biniou (FoxF), a central component in a regulatory network controlling visceral mesoderm development and midgut morphogenesis in Drosophila - Zaffran, Stéphane; Küchler, A; Lee, Hsiu-Hsiang; Frasch, Manfred (Genes & Development, 2001)
The subdivision of the lateral mesoderm into a visceral (splanchnic) and a somatic layer is a crucial event during early mesoderm development in both arthropod and vertebrate embryos. In Drosophila, this subdivision leads to the differential development of gut musculature versus body wall musculature. Here we report that biniou, the sole Drosophila representative of the FoxF subfamily of forkhead domain genes, has a key role in the development of the visceral mesoderm and the derived gut musculature. biniou expression is activated in the trunk visceral mesoderm primordia downstream of dpp, tinman, and bagpipe and is maintained in all types of developing gut muscles. We show that biniou activity is essential for maintaining the distinction between splanchnic and somatic mesoderm and for differentiation of the splanchnic mesoderm into midgut musculature. biniou is required not only for the activation of differentiation genes that are expressed ubiquitously in the trunk visceral mesoderm but also for the expression of dpp in parasegment 7, which governs proper midgut morphogenesis. Activation of dpp is mediated by specific Biniou binding sites in a dpp enhancer element, which suggests that Biniou serves as a tissue-specific cofactor of homeotic gene products in visceral mesoderm patterning. Based upon these and other data, we propose that the splanchnic mesoderm layers in Drosophila and vertebrate embryos are homologous structures whose development into gut musculature and other visceral organs is critically dependent on FoxF genes.
Keywords: visceral mesoderm; splanchnic mesoderm; midgut; mesoderm induction; forkhead/winged helix domain